Microsoft Sharepoint 2016 step by step - Londer, Olga; Coventry, Penelope (Step by step (Redmond, Wash.), 2016)
A guide to Microsoft SharePoint 2016 covers such topics as setting up a team site, organizing content into libraries, using blogs and wikis, and automating business processes with workflows.